Pengaruh Gratitude dan Peer Support terhadap Resilience Mahasiswi di Asrama Al-Hamdani - Mirza Aaliyah Agung; Iin Tri Rahayu; Ali Ridho; Muallifah Muallifah; Fathul Lubabin Nuqul (Program Studi Psikologi Islam, 2026)
Female students living in dormitories encounter various academic, social, and emotional challenges that require resilience to adapt effectively. Gratitude and peer support are considered important factors that help individuals cope with pressures and challenges during dormitory life. This study aimed to examine the influence of gratitude and peer support on resilience among female students residing in Al-Hamdani Dormitory. A quantitative approach with a cross-sectional design was employed. The participants were 105 female students selected using a total sampling technique. Data were collected using gratitude, peer support, and resilience scales that met validity and reliability requirements. Multiple linear regression analysis was used to test the hypotheses. The results showed that gratitude and peer support simultaneously had a positive and significant effect on resilience, F(2,102) = 181.66, p < .001, explaining 78.1% of the variance in resilience (R² = .781). Partially, gratitude (t = 6.10, p < .001) and peer support (t = 3.65, p < .001) were significant predictors of resilience. These findings indicate that higher levels of gratitude and stronger peer support are associated with higher resilience among female students in coping with academic demands, social adjustment, and challenges of dormitory life. This study contributes empirical evidence regarding resilience within a dormitory-based educational setting that remains relatively underexplored in Indonesian psychological research.